2017
DOI: 10.1016/j.jns.2017.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Addressing post-stroke care in rural areas with Peru as a case study. Placing emphasis on evidence-based pragmatism

Abstract: Stroke is a major cause of death and disability, with most of its burden now affecting low- and middle-income countries (LMIC). People in rural areas of LMIC who have a stroke receive very little acute stroke care and local healthcare workers and family caregivers in these regions lack the necessary knowledge to assist them. Intriguingly, a recent rapid growth in cell-phone use and digital technology in rural areas has not yet been appropriately exploited for health care training and delivery purposes. What sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 83 publications
0
19
0
4
Order By: Relevance
“…Timely care is essential for stroke patients and the lack of specific stroke units can be a barrier here, however, in this case, other options such as transfers to another medical facility and telemedicine for assessment and thrombolysis may be of some use as there is often limited access to physicians and diagnostic services . Interventions such a telemedicine, or e‐health and other technology‐based interventions have been utilised to assist healthcare professionals to provide specialist stroke care in rural or remote areas in many regions worldwide . This form of care, although not always relevant to every stroke case, may deliver on several evidence‐based practices that are currently lacking in Australian rural areas, such as staff resources, medical training and specialist consultation as well as areas of preventative health care and health promotion activities related to stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely care is essential for stroke patients and the lack of specific stroke units can be a barrier here, however, in this case, other options such as transfers to another medical facility and telemedicine for assessment and thrombolysis may be of some use as there is often limited access to physicians and diagnostic services . Interventions such a telemedicine, or e‐health and other technology‐based interventions have been utilised to assist healthcare professionals to provide specialist stroke care in rural or remote areas in many regions worldwide . This form of care, although not always relevant to every stroke case, may deliver on several evidence‐based practices that are currently lacking in Australian rural areas, such as staff resources, medical training and specialist consultation as well as areas of preventative health care and health promotion activities related to stroke.…”
Section: Discussionmentioning
confidence: 99%
“…10 Interventions such a telemedicine, or e-health and other technology-based interventions have been utilised to assist healthcare professionals to provide specialist stroke care in rural or remote areas in many regions worldwide. 17 This form of care, although not always relevant to every stroke case, may deliver on several evidence-based practices that are currently lacking in Australian rural areas, such as staff resources, medical training and specialist consultation as well as areas of preventative health care and health promotion activities related to stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The statements with the least influence on the use of eRehabilitation were comparable for BHP and DHP, and were related to patient characteristics and resources. This means that BHP and DHP indicate that the use of eRehabilitation is influenced by different factors and tailored implementation strategies for both countries need to be developed separately (16).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in western countries concluded that eRehabilitation programs are generally considered feasible (5), however, in low-and middle income countries, future trails on the feasibility are needed (15). Furthermore, it has been shown that eRehabilitation interventions need to address culture-specific issues in order to be effective (23), however, eRehabilitation interventions for patients are rarely culturally-adapted (16).…”
Section: Contributions To the Literaturementioning
confidence: 99%
See 1 more Smart Citation